Hydrocarbon biodegradation and dynamic laser speckle for detecting chemotactic responses at low bacterial concentration - Nisenbaum, Melina (2014)
We report on the biodegradation of pure hydrocarbons and chemotaxis towards these compounds by an isolated chlorophenol degrader, Pseudomonas strain H. The biochemical and phylogenetic analysis of the 16S rDNA sequence identified Pseudomonas strain H as having 99.56% similarity with P. aeruginosa PA01. This strain was able to degrade n-hexadecane, 1-undecene, 1-nonene, 1-decene, 1-dodecene and kerosene. It grew in the presence of 1-octene, while this hydrocarbons is toxic to other hydrocarbons degraders. Pseudomonas strain H was also chemotactic towards n-hexadecane, kerosene, 1-undecene and 1-dodecene. These results show that this Pseudomonas strain H is an attractive candidate for hydrocarbon-containing wastewater bioremediation in controlled environments. Since the classical standard techniques for detecting chemotaxis are not efficient at low bacterial concentrations, we demonstrate the use of the dynamic speckle laser method, which is simple and inexpensive, to confirm bacterial chemotaxis at low cell concentrations (less than 105 colony-forming unit per millilitre (CFU/mL)) when hydrocarbons are the attractants.